Infrastructures of Dis/Connection: Of Drones, Migration, and Digital Care (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | Migration from sub-Saharan Africa to Northern Europe is imagined and visualized as the movement of human bodies along different territories, eventually traversing the geographically locatable line of the EU border. What this conceptualization of migration, mobility, and the border leaves unacknowledged is that all three are material-virtual phenomena. This paper addresses the infrastructures of mobility that can be traced and analyzed within a migrant route from Niger to Germany. We highlight the need to connect and/or disconnect as strategies of migration and envisage ways to support freedom of movement by bringing aspects of digital care work into the analysis.Résumé | La migration de l’Afrique subsaharienne vers l’Europe du Nord est imaginée et visualisée comme le mouvement des corps sur différents territoires, traversant éventuellement la ligne géographiquement localisable de la frontière de l’UE. Ce que cette conceptualisation de la migration, de la mobilité et de la frontière ne reconnaît pas, c’est que les trois sont des phénomènes matériels et virtuels. Cet article aborde les infrastructures de mobilité qui peuvent remontées et être analysées au sein d’une route migrante allant du Niger à l’Allemagne. Nous soulignons la nécessité de se connecter et/ou de se déconnecter en tant que stratégies de migration et envisageons des moyens d’appuyer la liberté de circulation en intégrant des aspects du travail en soins numériques dans l’analyse.